INTERFERENSI GRAMMATIKAL BAHASA INDONESIA DALAM BAHASA INGGRIS: KASUS PADA BUKU LKS BAHASA INGGRIS UNTUK SLTP DI SURAKARTA - Endang Fauziati (Jurnal Penelitian Humaniora, 2016)
The present study deals with Indonesian interference in English. It aims at giving a thick explanation about grammatical interference which especially exists inEnglish Workbooks for Junior High School students in Surakarta. The data consist of sentences containing interference taken from 10 English workbooks as data source. There were 185 sentences collected as data which were analyzed using error analysis framework and sociolinguistic perspective. The research findings show that there were seven types of grammatical interference: mismatching (62/33.51%), preposition(35/18.91%), superflous expression (27/14.59%), parallel construction (21/11.35%), passive (17/918%), conjunction (14/7.56%), and modifier and adverb (9/4.86%). Only one out of 10 workbooks, that is LKS Bahasa Inggris by MGMP, contained no language interference. The other 9 books contained language interference with the highest frequency occurred in LKS Bahasa Inggris RABEL (45/24.32%) and thelowest in LKS Bahasa Inggris Komunikasi Aktif (1/0.5%). The study also shows that the interference was due to two factors: the bilinguality of the book writers and the tendency of transferring old linguistic behavior in the new one (from Indonesian to English), which basically due to the writers’ constrains in English grammar.